2022
DOI: 10.1021/jacs.2c07023
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of the Brønsted Acidic Properties of Crabtree-Type Catalysts in the Asymmetric Hydrogenation of Olefins

Abstract: Chiral iridium complexes derived from Crabtree’s catalyst are highly useful in modern hydrogenations of olefins attributed to high reactivity, stereoselectivity, and stability. Despite that these precatalysts are pH neutral, the reaction mixtures turn acidic under hydrogenation conditions. This Perspective is devoted to the implications of the intrinsic Brønsted acidity of catalytic intermediates in asymmetric hydrogenation of olefins. Despite that the acidity has often been used only as a rationale for side-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…The dominant product in this reaction ( 2 d ) was generated through cleavage of the alcohol moiety, leaving the tetrasubstituted olefin untouched. Iridium‐based hydrogenation catalysts have been shown to form Brønsted‐acidic intermediates as part of the catalytic cycle, which can cause the formation of undesired side products in acid‐sensitive substrates [3i,11] . Allylic alcohols like compound 1 are frequently susceptible to acid‐catalyzed elimination and subsequent hydrogenation of the more accessible olefin [12]…”
Section: Resultsmentioning
confidence: 99%
“…The dominant product in this reaction ( 2 d ) was generated through cleavage of the alcohol moiety, leaving the tetrasubstituted olefin untouched. Iridium‐based hydrogenation catalysts have been shown to form Brønsted‐acidic intermediates as part of the catalytic cycle, which can cause the formation of undesired side products in acid‐sensitive substrates [3i,11] . Allylic alcohols like compound 1 are frequently susceptible to acid‐catalyzed elimination and subsequent hydrogenation of the more accessible olefin [12]…”
Section: Resultsmentioning
confidence: 99%
“…Bidentate (mixed donor) chiral ligands developed by Pfaltz et al [58] and Andersson et al [59] are mostly used in Ir-catalyzed asymmetric hydrogenation of olefins. On the other hand, the use of chiral monodentate phosphines in Ir-catalyzed enantioselective hydrogenation is uncommon.…”
Section: Catalysismentioning
confidence: 99%
“…However, quaternary alcohols are for obvious reasons not directly accessible via asymmetric hydrogenation. Iridium-hydride complexes are considered as potential Lewis acids and/or Brønsted acids in certain cases . In 2010, Burgess reported that many N,P-based Ir-complexes have a Brønsted acidity similar to acetic acid .…”
Section: Introductionmentioning
confidence: 99%